The Theory of Predicative and Enunciative Operations point of view on the reflexivity of SE in Brazilian Portuguese - Souza, Fátima Graziele de (2022)
This paper aims to study the reflexivity attributed to the pronoun SE as the product of the dynamics of enunciative contextualization’s in which it is inserted. The development of this research is based on Antoine Culioli's Theory of Enunciative Predicative Operations (CULIOLI, 1990, 1999a, 1999b). Our objective was supported by the operative analysis of markers sacrificar. The reflexivity of SE is dependent on the assertion marks of the enclosing context that allows moving from a possible reflexivity (predicate projection) to a de facto reflexivity (predicate occurrence). The reflexive value is based on the subjects' variable experience, and that they project such value on the SE, in the situation of production and interpretation of texts, that is, in the situation of language practice.